2020
DOI: 10.1111/bcp.14657
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of vancomycin in patients with external ventricular drain‐associated ventriculitis

Abstract: Running head: A pharmacokinetic model describing vancomycin in neurocritical care patients with ventriculitis was developed. Based on our analysis, the dosing of vancomycin should be referred to the degree of inflammation and renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…A linear three-compartmental model demonstrated that total vancomycin plasma clearance (Cl) depends on creatinine clearance and that CSF lactate concentration correlates with the clearance between the central and the CSF department. Therefore, Jalusic et al recommend the application of TDM and consider the degree of inflammation, measured by CSF lactate, and renal function for vancomycin dosing [ 20 ].…”
Section: Vancomycinmentioning
confidence: 99%
See 3 more Smart Citations
“…A linear three-compartmental model demonstrated that total vancomycin plasma clearance (Cl) depends on creatinine clearance and that CSF lactate concentration correlates with the clearance between the central and the CSF department. Therefore, Jalusic et al recommend the application of TDM and consider the degree of inflammation, measured by CSF lactate, and renal function for vancomycin dosing [ 20 ].…”
Section: Vancomycinmentioning
confidence: 99%
“…Therefore, the type of illness also impacts CSF drug penetration. Moreover, increased renal clearance, as often seen in ICU, affects antibiotic serum concentrations, leading to a different relation between dosing and CSF concentration [ 19 , 20 ]. Therefore, enhanced renal clearance must be considered to prevent underdosing in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The drug loss from CSF can be described by the clearance of the CSF compartment (CL CSF ), which was related to the average daily drainage amount (DA) and the elapsed time (ET) after IVT injection. Similarly, a recent PK study for patients with EVD-associated ventriculitis conducted by Jalusic et al (2021) built a three-compartment model with two elimination pathways. They found CSF lactate levels as a substitute for inflammatory processes may be associated with increased CSF vancomycin concentration.…”
Section: Effects Of Patients-specific Factors On Vancomycin Pk/pd For...mentioning
confidence: 99%